2014
DOI: 10.1186/1471-2164-15-415
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Mycobacterium avium subsp. paratuberculosis-specific genes impairs in vivo fitness

Abstract: BackgroundMycobacterium avium subsp. paratuberculosis (MAP) is an obligate intracellular pathogen that infects many ruminant species. The acquisition of foreign genes via horizontal gene transfer has been postulated to contribute to its pathogenesis, as these genetic elements are absent from its putative ancestor, M. avium subsp. hominissuis (MAH), an environmental organism with lesser pathogenicity. In this study, high-throughput sequencing of MAP transposon libraries were analyzed to qualitatively and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 57 publications
5
42
0
Order By: Relevance
“…Though a sensible genetic approach was used, the screening method is labour intensive to screen a representative mariner transposon library. More recently, a larger study was performed that collected 90 000 Himar1 mutants but identified insertions in approximately 12 000 out of 52 000 (ca 25 %) recognition sites (Wang et al, 2014). Wang et al (2014) attributed this low number of recognition sites represented to bottle-necking effects during DNA sample preparation or the sequencing stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though a sensible genetic approach was used, the screening method is labour intensive to screen a representative mariner transposon library. More recently, a larger study was performed that collected 90 000 Himar1 mutants but identified insertions in approximately 12 000 out of 52 000 (ca 25 %) recognition sites (Wang et al, 2014). Wang et al (2014) attributed this low number of recognition sites represented to bottle-necking effects during DNA sample preparation or the sequencing stage.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a larger study was performed that collected 90 000 Himar1 mutants but identified insertions in approximately 12 000 out of 52 000 (ca 25 %) recognition sites (Wang et al, 2014). Wang et al (2014) attributed this low number of recognition sites represented to bottle-necking effects during DNA sample preparation or the sequencing stage. However, loci-dependent transposition biases are more likely to explain these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…avium, and M. avium ssp. paratuberculosis that are shared by different animal species including primates (Pal,2007;Wang et al, 2014). These pathogens resist adverse environmental conditions (Verma, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, M.avium subspecies paratuberculosis (MAP) has emerged as a major and successful animal pathogen with significant zoonotic, and public health concerns since first observed by Johne and Frothingham in 1895 (Pal,2007;OIE,2008).MAP is an intracellular pathogen that causes Johne's disease(JD), a chronic (2 to 5 years) intestinal inflammation in cattle, sheep, goats, and wild deer etc. species including primates (Pal,2007;Wang et al, 2014). JD is a chronic granulomatous bowel inflammatory condition in animals provoked by progressive weight loss resulting death.The World Organization for Animal Health (OIE) considers JD as a disease of major global importance.…”
Section: Introductionmentioning
confidence: 99%